Leadership in the era of digital transformation through the integration of modern management technologies and time management in the manufacturing sector. - Krainik, Olena; Sergiienko, Tetiana; Loza, Svitlana (Management and Entrepreneurship: Trends of Development, 2025)
The article examines the transformation of leadership in production management under the influence of digital technologies, automation, and modern time-management systems. Digital transformation fundamentally reshapes managerial roles, strengthening the importance of data-driven decision-making, process transparency, and rapid adaptation to dynamic production environments. New leadership competencies—such as digital literacy, the ability to work with analytical tools, and the use of agile and flexible management methodologies—become essential for ensuring organisational effectiveness and maintaining competitiveness. The purpose of the study is to justify the role of modern management technologies and digital time-management tools in forming effective leadership models within industrial enterprises. The research methodology integrates the analysis of scientific publications on digital transformation and leadership development, a systems approach to identifying links between technological innovations and team performance, as well as comparative and structural analysis of management practices in leading manufacturing companies. The study demonstrates that digitalisation enhances the value of adaptive, transformational, and service-oriented leadership connected to project-management platforms, productivity-monitoring systems, artificial intelligence applications, and time-optimisation algorithms. It is shown that the integration of technological solutions with time-management approaches creates a new model of leadership effectiveness, characterised by accelerated communication, the automation of routine tasks, optimisation of workloads, and improved coordination of production processes. The practical significance of the research lies in the potential to apply these approaches to increase productivity, strengthen digital competencies among leaders, support continuous improvement, and promote an innovative organisational culture within industrial environments.JEL Classification: М11, М12, М15, О32, О33